Pengaruh Media Pembelajaran Daring Terhadap Pengetahuan Belajar Mahasiswa Akuntansi - Sherina Karyanto; Reynard Tandayu; Jessica Febriani; Tan Ming Kuang (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2020)
Instructional media is one of important factors that affect students’ understanding on the learning materials. The main purpose of this study is to examine the impact of instructional media especially e-learning on students’ knowledge in a business education context based on E-learning theory. Data collected from 80 valid respondents at two well-known private universities in Bandung were used to test the research hypothesis using simple regression method. The results indicate that e-learning is perceived as a useful approach for helping accounting students acquire knowledge. This study implies that e-learning may be considered as one approach to deliver knowledge in a business education domain.